Chapter Developing Functionality in Perovskites from Abatement of Pollutants to Sustainable Energy Conversion and Storage - Bedon, A. (InTechOpen, 2020)
Different functionalities can be developed and optimised in perovskites by means of different approaches: doping, nanocomposition and exsolution. In our research, these strategies are used with the aim of a sustainable development. Our objectives are in developing perovskite-based materials for catalysis and electro-catalysis. In particular, we successfully obtained catalysts for abatement of pollutants in three-way catalysts, catalysts for dry reforming of methane and electro-catalysts for solid oxide cells (solid oxide fuel cells and solid oxide electrolysers). In all cases, the corresponding device and experimental set-up was optimised. The catalysts and electro-catalysts we considered are free of noble metals and with minimum amount of critical raw materials. The preparation procedures are by wet chemistry, highly reproducible and up-scalable.